A Comparative Study of Grades 7, 8 and 9 Students’ Motivation for Learning English as A Foreign Language in The Regular Program and English Program at Tepleela School, Bangkok, Thailand - Aguilar Concepcion, Evangeline; Ye, Yan (Scholar: Human Sciences, 2018)
This study aimed to identify the levels of intrinsic and extrinsic motivation for grades 7, 8 and 9 students to learn English as foreign language in the Regular Program and in the English Program firstly; then, to compare the students’ intrinsic and extrinsic motivation to learn English as a foreign language between the Regular and English Program. The participants of this study were 253 students from grade 7, 8, and 9 of the Regular and English Program studying English as a foreign language at Tepleela School, Bangkok, Thailand. The study used MALESC questionnaire, which was composed of 19 statements on intrinsic and extrinsic motivation. The findings of this study were: 1) the levels of intrinsic and extrinsic motivation to learn English as a foreign language in the Regular Program was high; 2) the levels of intrinsic and extrinsic motivation to learn English as a foreign language in the English Program was high; 3) there was no significant difference in students’ intrinsic motivation to learn English as a foreign language between the Regular and English Program; 4) There was a significant difference in students’ extrinsic motivation to learn English as a foreign language between the Regular and English Program.